Gathering at home of Bruce and Linda Bronzan - Watkins, Howard K. (1977)
Living room gathering: Shayna Brodie, Peggy Bronzan, Leonel Alvarado, Bob Quesada, Beth Meyerson, Doug Jones, Art Dyson, Jim Dockery, Bernie Meyerson, ? Linda Bronzan, Mike Bauernfeind, ?, ?